2000
DOI: 10.1007/s003350010053
|View full text |Cite
|
Sign up to set email alerts
|

Mater encodes a maternal protein in mice with a leucine-rich repeat domain homologous to porcine ribonuclease inhibitor

Abstract: MATER (Maternal Antigen That Embryos Require) is an ooplasm-specific protein first identified as an antigen (OP1) associated with ovarian autoimmunity in mice. Its primary structure has been deduced from full-length cDNA that encodes a 125-kDa protein required for progression of the mouse embryo beyond two cells. Expression of the gene encoding MATER is restricted to the oocyte, which makes it one of a growing, but still limited, number of maternal-effect genes in mammals. To further investigate the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…In this study, we have documented the multiple oocyte Ag to which the autoimmune responses of d3tx B6AF1 mice are directed. The 110-kDa oocyte Ag, which may elicit the earliest autoimmune response, has been characterized by Tong and Nelson (17) as a prefertilization oocyte protein required for blastocyst formation after fertilization (25). In this study, we have shown clearly that the transcript for this oocyte autoantigen is detectable in B6AF1 ovaries on the day of birth, and that oocyte Ag are recognized by autoantibodies 1 day later, and by CD4 T cells as early as 3 days later.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, we have documented the multiple oocyte Ag to which the autoimmune responses of d3tx B6AF1 mice are directed. The 110-kDa oocyte Ag, which may elicit the earliest autoimmune response, has been characterized by Tong and Nelson (17) as a prefertilization oocyte protein required for blastocyst formation after fertilization (25). In this study, we have shown clearly that the transcript for this oocyte autoantigen is detectable in B6AF1 ovaries on the day of birth, and that oocyte Ag are recognized by autoantibodies 1 day later, and by CD4 T cells as early as 3 days later.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, multiple approaches have been undertaken to identify genes preferentially expressed in the oocyte and embryo, and two new key genes in mouse models, including factor in the germline (Figla), newborn ovary homeobox gene (Nobox), were obtained (Liang et al, 1997;Rajkovic et al, 2004). Besides, there are some other oocyte-and embryo-specific genes, including growth differentiation factor 9, Gdf9 (McGrath et al, 1995), maternal antigen that embryos require, Mater (Tong et al, 2000), zygote arrest 1, Zar1 (Wu et al, 2003) and neurotrophins (NTs) (Paredes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mater, the oocyte-speci®c maternal protein has an Nterminal uncharacterized domain, central NOD and Cterminal LRRs (Tong and Nelson, 1999;Tong et al, 2000a). Although the molecular function of Mater remains unknown, the null Mater mutation is lethal at the two-cell embryo stage, suggesting that Mater plays an essential role on cell viability at early stages of embryogenesis (Tong et al, 2000b).…”
Section: Nods: a Family Of Nod-containing Proteinsmentioning
confidence: 99%